Controle alternativo de oídio em abobrinha de moita com solução de vinagre. - Nakada-Freitas, Pâmela Gomes [UNESP]; Sandri, Miguel Ângelo [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP]; Eberhardt Neto, Erich [UNESP] (Fundacao Educational de Ituverava, 2014)
Alternative methods and products to control diseases in plants are growing among horticultural species producers. Diseases as powdery mildew can bring loss to producers. Several products are using instead pesticides, but there is a lack of information about its efficiency. This study aimed to evaluate the effect of vinegar solutions to control powdery mildew in zucchini squash. The treatments consisted of six solutions: 0 (water), 4, 8, 12 and 16% of wine vinegar and a chemical control (fenarimol at 0.3 mL.L-1 ). A weekly application was done, from the onset of symptoms (44 days after sowing), totalizing six application to control powdery mildew. The experimental design was a randomized block with four replications and six plants per plot considering four plants available. A total of five evaluation of disease severity (% of leaf area with symptoms of the disease), at 51, 58, 65, 72 and 79 days after sowing were done. It is concluded that solutions of vinegar (4-16%) weren’t effective in controlling powdery mildew in zucchini squash, and that high concentrations burn the leaves.

O interesse por métodos e produtos alternativos para o controle de doenças vem crescendo entre os produtores de hortaliças. Doenças como o oídio, podem trazer prejuízos aos produtores se não forem controladas a tempo. Vários produtos têm sido usados como alternativa aos tradicionais agroquímicos, no entanto, são poucas as informações obtidas quanto a eficiência destes. Este trabalho teve como objetivo avaliar o efeito de soluções de vinagre para o controle de oídio em abobrinha de moita. Os seis tratamentos consistiram de soluções a 0, 4, 8, 12 e 16% de vinagre de vinho tinto e uma testemunha com controle químico (fenarimol a 0,3 mL L-1 ). Foi realizada uma aplicação semanal, a partir do aparecimento dos primeiros sintomas (44 dias após a semeadura), totalizando seis aplicações para o controle do oídio. O delineamento foi em blocos ao acaso, com quatro repetições e seis plantas por parcela considerando-se quatro plantas úteis. Foram realizadas cinco avaliações de severidade (% da área foliar com sintomas da doença), aos 44; 51; 58; 65 e 72 dias após a semeadura. As soluções de vinagre (4 a 16%) não diminuíram a incidência de oídio. Nas maiores concentrações de vinagre (12 e 16%) ocorreu queima de folhas.
Alternative control of powdery mildew in zucchini squash with vinegar solutions
Keywords: Cucurbita pepo; Podosphaera xanthii; Severity; Cucurbita pepo; Podosphaera xanthii; Severidade